Azurduy por Anzoátegui: subjetividad femenina y espacio público en Huallparrimachi (1894) - Suárez, Mariana Libertad (2018)
This research looks at the tensions between the notion of universal law defended by republican liberalism at the turning-point of the 19th to the 20th century and the demands for participation in the political, social and cultural fields by intellectual women. In those years, female narrators, poets and playwrights made of historical fictions a territory of symbolic dispute, a field from which to express their dissatisfaction and expose their claims. From this framework, I will propose a review of Huallparrimachi (1894), by the Bolivian writer Lindaura Anzoátegui, in which the historical figure of Juana Azurduy is appropriate as a resource for self-writing and used to reflect about the entrance of women to the spaces of political decision making.